Retraction notice to “An analysis of the engineering properties of mortars containing corn cob ash and polypropylene fibre using the Taguchi and Taguchi-based Grey relational analysis methods” [Case Stud. Constr. Mater. 15 (2021) e00652] (Case Studies in Construction Materials (2021) 15, (S2214509521001674), (10.1016/j.cscm.2021.e00652)) - Arıcı, Erdinç; Çelik, Emrah; Keleştemur, Oğuzhan (Elsevier Ltd, 2022)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal). This article has been retracted at the request of the Editor(s)-in-Chief. The article duplicates significant parts of a paper that had already appeared in Construction and Building Materials, 297 (2021), 123792. https://doi.org/10.1016/j.conbuildmat.2021.123792. One of the conditions of submission of a paper for publication is that authors declare explicitly that the paper has not been previously published and is not under consideration for publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a misuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process. © 2022 The Authors